Sistem Informasi Pengarsipan Surat Masuk Dan Surat Keluar Berbasis Website Dan Whatsapp Gateway Di LPP RRI Pekanbaru - Ayunda Widia Kusuma; Noveri Lysbetti Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
In processing data on incoming and outgoing letters in LPP RRI Pekanbaru conducted by the secretary still has shortcomings namely the incoming and outgoing mail files have not been well organized. Inefficient in the process of searching for incoming and outgoing mail files, the secretary has to search one by one the letters stored in the folder, not to mention that the file is missing or scattered then it will take a long time to find the file. The purpose of this research is to create a web-based incoming and outgoing mail archiving information system and whatsapp gateway in LPP RRI Pekanbaru so that it can streamline the time in searching, data collection and making reports of incoming and outgoing letters. The programming language used in Information System Design is PHP Hypertext Preprocessor (PHP), Hypertext Markup Language (HTML), Javascript, and My Structured Query Language (MYSQL). While the system development method used is the Waterfall method. The results of the test based on the Likert calculation formula are as expected. And the Presentation Accuracy of the Questionnaire is 82.5, so the system is very amenable to use. The conclusion of this research is that it can facilitate the processing of letter data, the process of making reports, and facilitate the process of finding data.Keyword : Information System, Incoming Letters, Outgoing Letters, Disposition